Mitigation Measures for Climate Change: An Environmental and Public Health Emergency - Marcelo Augusto Kessler Machado; Rosa Isabel de Araujo Bordignon; Ubiratan Alegransi Bones; Leticia de Lima Trindade; Maria Assunta Busato; Vanessa da Silva Corralo; Junir Antônio Lutinski (Archives of Current Research International, 2025)
The Intergovernmental Panel on Climate Change (IPCC), established in 1988, is an international organization responsible for assessing climate change, its progression, and associated impacts. To date, six Assessment Reports (AR1 to AR6) have been published, presenting the scientific foundations, observed and projected effects, as well as mitigation and adaptation strategies. The objective of this study was to evaluate the main environmental and human health impacts described in the IPCC reports, as well as to identify the mitigation measures recommended. The methodology employed consisted of a systematic documentary review of the six IPCC Assessment Reports: AR1 (1990), AR2 (1997), TAR (2001), AR4 (2007), AR5 (2014), and AR6 (2021). The reviewed documents highlight a range of environmental impacts, including the rise in average global temperatures, sea level rise, and the increasing frequency and intensity of extreme weather events. In the field of health, notable concerns include the rise in heat-related illnesses, respiratory diseases, vector-borne outbreaks, and threats to food and water security. Among the identified mitigation strategies are the transition to renewable energy sources, the adoption of sustainable agricultural practices, and the development of integrated policies with differentiated responsibilities. The implications of this study emphasize the urgency of implementing strong public policies and coordinated actions among governments, businesses, and communities, with the goal of building a sustainable and resilient development model. Adopting these measures is essential for protecting the environment and public health for current and future generations.